Effects of added zinc during the grower and/or finisher phase on growth performance and carcass characteristics of finishing pigs fed diets with or without ractopamine HCl - Paulk, Chad B.; Tokach, Michael D.; Dritz, Steven S.; Gonzalez, John M.; DeRouchey, Joel M.; Goodband, Robert D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2015)
A total of 1,197 pigs (PIC 337 × 1050) were used in a 72-d study to determine the effects of added zinc from zinc oxide (ZnO) fed in grower (d 0 to 45; initially 129.6 lb) and finisher (d 45 to 72; initially 218.3 lb) pig diets with or without ractopamine HCl (RAC; Paylean; Elanco Animal Health, Greenfield, IN) on growth performance and carcass characteristics. Pens were randomly assigned to a 2 × 2 × 2 factorial arrangement in a split-plot design. The whole plot consisted of diets with or without 75 ppm added Zn from d 0 to 45, and the subplots were diets with or without 75 ppm added Zn and with or without 10 ppm RAC from d 45 to 72. All diets contained 50 ppm Zn supplied from the premix. No interactions were observed. Addition of 75 ppm Zn during either period or both periods did not influence overall pig growth performance or carcass characteristics. Pigs fed RAC had improved (P < 0.03) ADG, F/G, final BW, HCW, loin depth, and fat-free lean index compared with pigs fed the control diet. In conclusion, feeding RAC improved the performance of growing-finishing pigs, but additional Zn did not.
Swine Industry Day, 2014 is known as Swine Day, 2014
Keywords: Finishing pig; Ractopamine HCl; Zinc